Endovascular treatment of ruptured anterior circulation aneurysms within 24 hours: Clinical and angiographic results - Kolu, Mehmet; Cigdem, Gulyara; Dere, Osman; Kaya, Veysel; Okan Yildirim, Ismail; Sarac, Kaya (Annals of Medical Research, 2021)
Aim: In this study, angiographic and clinical results after endovascular treatment were evaluated in patients with a ruptured brain aneurysm.Materials and Methods: A total of 32 patients, who admitted to the hospital between May 2018 and January 2020 due to aneurysmal subarachnoid hemorrhage (SAH), were included in the study. Cranial digital subtraction angiography (DSA) imaging was performed within the first 24 hours to patients with SAH detected on computed tomography and endovascular embolization was performed in 32 patients, who were considered as suitable for endovascular treatment. The pretreatment clinical scorings of the patients were evaluated according to the Hunt-Hess scale. Aneurysm occlusion was performed according to the Raymond-Ray classification. The patients were evaluated with the clinical outcome modified ranking scale (mRS) during their follow-up periods.Results: The endovascular treatment was successfully performed in all patients. In the first angiograms for control purposes after embolization, it was seen that the aneurysms were completely closed (RR1) in 81.25%, partial neck remained (RR2) in 12.5%, and the aneurysms were closed incompletely (RR3) in 6.25% of the patients. Intraprocedural complications developed in five patients (15.6%). There was an aneurysmal rupture in 1 patient (3.1%) and thromboembolic complications in 4 patients (12.5%). The procedure-related morbidity and mortality rates were 9.3% and 3.1%, respectively. No patients had postprocedural hemorrhagic complications. In the 3rd month, mRS was 0 in 21 (65.6%) patients, 1 (3.1%) in 1 patient, and 2 (6.25%) in 2 patients. A total of 11 (34.3%) patients died. A second procedure was performed in 2 (6.25%) of the patients who were followed because there was an RR3 residue.Conclusion: The endovascular embolization process can be applied in the treatment of intracranial aneurysms causing subarachnoid hemorrhage, and it is a safe and effective treatment method.
Keywords: Brain aneurysm; Endovascular treatment; Subarachnoid hemorrhage